2020
DOI: 10.3390/nu12082203
|View full text |Cite
|
Sign up to set email alerts
|

A Dairy Product to Reconstitute Enriched with Bioactive Nutrients Stops Bone Loss in High-Risk Menopausal Women without Pharmacological Treatment

Abstract: Osteoporosis is a multifactorial disease characterized by the loss of bone mass and deterioration of the internal structure of the bone, increasing the risk of fractures, and is becoming an economic and social problem. The main treatment is pharmacological, however, the population demands other therapies, such as foods with nutrients beneficial to bone health. Seventy-eight healthy menopausal women at risk of osteoporosis or untreated osteopenia were recruited for a randomized, parallel, double-blind clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…However, compared to the decrease in OC levels in the control group, OC levels were maintained in the study group. [17,18,20] Furthermore, a significant correlation between the changed concentration of L. fermentum SRK414 and OC was observed at 3 months post-trial. In most cases, bone formation and resorption markers are coupled and change in the same direction.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, compared to the decrease in OC levels in the control group, OC levels were maintained in the study group. [17,18,20] Furthermore, a significant correlation between the changed concentration of L. fermentum SRK414 and OC was observed at 3 months post-trial. In most cases, bone formation and resorption markers are coupled and change in the same direction.…”
Section: Discussionmentioning
confidence: 81%
“…[21] OC is currently in the spotlight showing its capacity beyond bone metabolism in organs like myofibrillar fiber as well as muscle mass. [20] OC regulates bone quality by aligning biological apatite parallel to collagen fibrils, which is important for bone strength to load the direction of the long bones. [22] Further study is needed to determine the mechanism of OC.…”
Section: Discussionmentioning
confidence: 99%
“…The CLA isomers contained in sheep milk may induce beneficial effects on human health, such as “anti-cancer” properties, lower triglyceride concentrations, and reduced blood cholesterol and glucose levels [ 5 , 51 , 52 ]. These isomers also normalize the functions of the immune system [ 53 , 54 ]. The cis-9, trans-11 CLA, and trans-10, cis-12 CLA isomers affect specific T cell populations and immunoglobulin subclasses.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the subjects who consumed the enriched product had higher levels of bone metabolism markers than the placebo group. This suggests that the consumption of a dairy product enriched in these nutrients (including vitamin K) may represent a primary prevention method against osteoporosis [ 132 ].…”
Section: Discussionmentioning
confidence: 99%